The value of work: Addressing the future of work through the lens of solidarity - Prainsack, Barbara; Buyx, Alena (Bioethics, 2018)
Designing the future of work is crucial to the health and well‐being of people and societies. Experts predict that developments such as the advancement of digital technologies, automation, and the movement of manufacturing jobs to low‐wage countries will lead to major transformations in the labour market, and some foresee significant job losses. Due to the close relationship between employment and health, major job losses would have significant negative impacts on the health and well‐being of individuals and societies. Job losses would also pose a major challenge to solidaristic support within societies because they would negatively affect the recognition of similarities among people, which is vital for solidaristic practice and institutions. To prevent these negative effects, a fundamental redesign of the relationship between work and income is necessary. And for this project to succeed, we need to reconsider of the value of work. Building on definitions of flourishing people and societies, we argue that the value of work should not be determined by the labour market, but according to its importance for society. Using a solidarity‐based framework we argue that such a revaluation of work will help to ensure social cohesion and increase reciprocity in our societies. It will serve as a foundation upon which we can reconfigure the relationship between work and income without risking the loss of social cohesion and solidarity.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Automation; Digitization; Employment; Future of work; Labour; Solidarity; Work